MiR-26a targets EphA2 to resist intracellular Listeria monocytogenes in macrophages. (December 2020) - Zhang, Jiale; Yuan, Jiangbei; Wang, Liting; Zheng, Zihan; Ran, Haiying; Liu, Fang; Li, Fei; Tang, Xiangyu; Zhang, Junying; Ni, Qingshan; Zou, Liyun; Huang, Yi; et al.
Graphical abstract: Highlights: miR-26a is down-regulated in macrophages cells during Lm infection. miR-26a inhibits the expression of EPHA2 in macrophages. The miR-26a/EphA2 axis may function during the phagosome escape process to control the proliferation of Lm . Abstract: At infection sites, macrophages are sentinels that resist and destroy various pathogens, through direct phagocytosis. In macrophages, microRNAs play a variety of crucial roles, the most striking of which is the regulation of the ability of the host cell to resist infection. However, the underlying mechanisms associated with the anti-infection effects mediated by microRNAs remain largely unknown. Here, we demonstrated that miR-26a is downregulated during infection by Listeria monocytogenes ( Lm ). In miR-26a overexpressing mice, the Lm bacterial burden of liver and spleen decreased significantly within 72 h of infection, compared with that in control mice. Subsequently, RNA sequencing (RNA-seq) data suggested that miR-26a may attenuate the survival of Lm by targeting the Ephrin receptor tyrosine kinase A2 (EphA2). The knockdown of EphA2 in RAW264.7 macrophage cells resulted in decreased intracellular Lm burden. Taken together, these findings validate EphA2 as a target of miR-26a and provide a mechanism through which Lm may survive within macrophages by altering host miRNA expression.